Priekulės spaustuvė - Kaunas, Domas (Knygotyra, 1976)
Priekulė, an old settlement of Klaipėda region, is mentioned in written sources from 1540. At the begining of Reformation there was founded a chapel (pryer house), the ministers of which had often been graduates of Karaliaučius and other universities. They are F. Masalskis (about 1558–1613) an examiner of the translation of J. Bretkūnas Bible, J. Aldas (about 1580–1642) a collaborator of L. Zengštokas, the author of the first Lithuanian agriculture guide D. Zetegastas (about 1730–1810) and some other collaborators of G. Neselmanas, A. Šleicheris, F. Kuršaitis, A. Becenbergeris. Developing capitalist relations made favourable conditions for the growth of Priekulė. In the middle of XIX century it had a great number of authority and trade institutions and good communications with the towns of all Western lands. In 1856 the head of orphan-asylum F. Srioderis founded a printing-house exeting to get some profit of it. He had been working as a printer for 10 years and during this period he published about 40 printings. Almost half of them were of secular contents, i. e. text-books, guides for practical work etc. It was his great merit because people at that time were stuffed with religious literature. From 1866 he started to publish the calendar “Evangeliškos kalendros”. From 1875 the printing-house of Priekulė passed to J. Traušys. Being famous of the religiousness and submissiveness to German monarchism he had gained great confidence of the authorities. That why in 1880 he was appointed to publish an organ of conservative party the newspaper “Tiesos prietelius”. From 1882 it was called “Konzervatyvų draugystės laiškas”. Several decades it was known as an antogonist to Lithuanian national interests. In Klaipėda region J. Traušys during his printing activity (he died in 1918) had published about 150 books, he continued publishing of calendars as well. Inspite of their religious narrowmindedness and inimical ideology these issues prevented from extermination the native language and fostered the society of readers. In periodicals one can find a great number of historical material and studies of local lore. Some progressive men such as M. Šernius, M. Kiošis, printers K. Kibelka, J. Martinaitis and others acquired their first habits of printing and publishing work in Priekulė printing-house.